2019
DOI: 10.19044/esj.2019.v15n3p223
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Mechanism of Friction and Wear Reduction Using Oil-Based ZnO Nanofluid Applied on Brass

Abstract: In this research, friction and wear characteristics of oil-based ZnO nanofluid applied on brass disk specimens using a flat-on-flat reciprocating sliding test were studied. Oleic acid was used as surfactant to improve the stability and dispersibility of the ZnO nanofluid. Metallurgical optical microscopy, scanning electron microscopy and energy-dispersive X-ray spectroscopy were utilized to understand the mechanisms. A 2wt% ZnO nanofluid resulted in 61.1% reduction in coefficient of friction. Good wear resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In the present research, the addition of OA only in PAO 4 base oil showed some benefits on the reduction of friction and wear. Similar results were also reported by Sophie et al [18] and Tao et al [19]. In addition, there were no significant differences in COF and wear rate in width and depth between 1 mass% and 3 mass%.…”
Section: Friction and Wear Losssupporting
confidence: 90%
“…In the present research, the addition of OA only in PAO 4 base oil showed some benefits on the reduction of friction and wear. Similar results were also reported by Sophie et al [18] and Tao et al [19]. In addition, there were no significant differences in COF and wear rate in width and depth between 1 mass% and 3 mass%.…”
Section: Friction and Wear Losssupporting
confidence: 90%